A place in the sun Haiti, Haitians, and the remaking of Quebec - Mills, Sean (Études d'histoire du Québec, 2016)
"What is the relationship between migration and politics in Quebec? How did French Canadians' activities in Haiti influence Quebec society? How did Haitian migrants shape debates about language, class, nationalism and sexuality? In exploring these questions, A Place in the Sun breaks new historiographical ground by challenging the traditional tendency to view migrants as peripheral to Quebec history. Mills begins by analyzing French-Canadians' early ideas about Haiti and their forays into the country. Missionaries, nationalist elites, and government officials produced an idea of Haiti as being linked to French Canada, yet fundamentally different from it and in need of its asssitance. The second part of the book reverses the perspective, and Haitians' ideas about Quebec take centre stage. Mills engages with the ideas and activities of taxi drivers, exiled priests, aspiring authors and feminist activists. From global political economy to the intimate realm of sexuality, he argues, Haitian migrants opened up new debates and exposed new tensions, along the way playing a key role in transforming Quebec society."--De l'éditeur